AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAN FRAKSI AKAR TABAR KEDAYAN (Aristolochia foveolata Merr.) DENGAN METODE DPPH (2,2 DIPHENYL-1-PICRILHYDRAZIL) - Risa Supringrum; Siti Jubaidah (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
Antioxidants are substances that can neutralize free radicals, thus protecting the body from various diseases by binding to free radicals and highly reactive molecules that can damage cells. The use of high-dose synthetic antioxidants is reported to be toxic and carcinogenic. Tabar Kedayan root (Aristolochia foveolata Merr) is one of the native plants from North Kalimantan, which is empirically used as an anti-poison, containing secondary metabolites including alkaloids, tannins, flavonoids. Flavonoids are powerful antioxidants. Some studies report that the function of flavonoids can be to prevent and treat cancer. This study aims to determine the antioxidant activity of ethanol extract and n-hexane fraction, the ethyl acetate fraction of Tabar Kedayan root with 2.2 Diphenyl- 1-Picrilhydrazil (DPPH) method as a free radical compound. The results of the study obtained IC50 values for each sample, at ethyl acetate fraction 267.48 ppm, ethanol extract at 603.80 ppm, ethanol-water fraction 705.43 ppm, n- hexane fraction 1500 ppm. The antioxidant activity tests indicate that ethyl acetate fraction is categorized as weak antioxidant, while the ethanol-water fraction and n-hexane fraction exhibit no antioxidant activity. Keywords : Tabar Kedayan, Antioxidants, 2.2 Diphenyl-1-Picrilhydrazil